An exploration of the relationships of experiential avoidance (as measured by the aaq-ii and meaq) with negative affect, perceived stress, and avoidant coping styles - M. Todd Allen (PeerJ, 2021)
Background Current psychotherapies seek to reduce experiential avoidance (EA) which has also been put forth as a risk factor for anxiety disorders, depression, and post-traumatic stress disorder. EA is a potentially maladaptive self-regulatory tendency to avoid negative thoughts, feelings, memories, physical sensations, and other internal experiences. One unresolved issue with the most commonly used measures of EA, the Acceptance and Action Questionnaire-II (AAQ-II) which measures EA as a single factor and the Multidimensional Experiential Avoidance Questionnaire (MEAQ) which measures EA as six subdimensions, is what exactly is being measured. The AAQ-II appears to measure negative affect (NA), some aspects of avoidant coping, and psychological distress. In addition, the relationships of all the MEAQ subscales have not been thoroughly examined with these other constructs. In the current study, the relationships of AAQ-II and MEAQ scores with NA, avoidant coping styles, and perceived stress were examined. Methods Two-hundred undergraduates (154 females and 46 males) completed the AAQ-II and MEAQ, the Distressed Type D Personality Scale (DS-14) which includes a measure of NA, the Brief COPE which measures coping styles, and the Perceived Stress Scale. Results Scores on the AAQ-II had moderate positive relationships with the MEAQ total score and all MEAQ subscales with the exception of distress endurance which had a moderate negative relationship. The AAQ-II had a stronger relationship with NA, avoidant coping, and perceived stress than did the MEAQ. All MEAQ subscales had a positive relationship to NA, avoidant coping, and perceived stress with the exception of distress endurance which had a negative relationship with these constructs. While the AAQ-II is limited as a unitary measure of EA the multiple dimensions of the MEAQ may involve an extraneous factor of distress endurance. Future work should examine the relationships of the MEAQ with NA, avoidant coping and perceived stress with clinical populations.